2008
DOI: 10.1111/j.1439-0531.2008.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ram Age on Structural and Functional Competence of Frozen-Thawed Spermatozoa in Dairy Sheep

Abstract: The objectives of this study were to investigate the influence of ram age on structural and functional competence of frozen-thawed spermatozoa and to test the hypothesis that increasing number of sperm bound to the zona pellucida in vitro was associated with decreasing in vivo fertility of frozen semen. Rams were allocated into two groups. Each group consisted of five rams aged either 1-2 years (young) or 4-5 years (mature). Three successive ejaculates were collected from each ram using an artificial vagina. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
5
2
Order By: Relevance
“…Previous studies reported seasonal changes in ram semen quality, while our results revealed that the ultrasonographic evaluation of testicular blood flow is also correlated with major semen characteristics depending on season. Lymberopoulos, Tsakmakidis, and Khalifa () reported that Chios rams of 4–5 years old (similar age with the adult rams group of our study) had better semen quality and in vivo fertility than younger rams of 1–2 years old. Furthermore, Batissaco et al.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies reported seasonal changes in ram semen quality, while our results revealed that the ultrasonographic evaluation of testicular blood flow is also correlated with major semen characteristics depending on season. Lymberopoulos, Tsakmakidis, and Khalifa () reported that Chios rams of 4–5 years old (similar age with the adult rams group of our study) had better semen quality and in vivo fertility than younger rams of 1–2 years old. Furthermore, Batissaco et al.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, most of the parameters evaluated were not significantly different between the abalone in the two age groups at respective spawning times. These results do not agree with the studies where sperm collected from older broodsotck produce a better ability to tolerate cryopreservation in comparison with their younger counterparts, such as found for rams (Lymberopoulos et al ) and white Italian ganders, Anser anser (Lukaszewicz et al ). However, caution should be taken as there was only 1 yr difference in age between the two age groups used in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, if sperm collected from 2‐yr‐old rather than 3‐yr‐old abalone can be cryopreserved for selective breeding, it can lead to substantial time and cost savings and economic benefits for breeding programs. However, the age of abalone may affect the ability of sperm to tolerate cryopreservation, as such age‐dependent effects have been detected in other species, such as Chios sheep (Lymberopoulos et al ) and rooster (Long et al ). The aim of this study was to test the hypothesis that broodstock age and sperm collection time in a natural spawning period can influence the ability of sperm to tolerate cryopreservation.…”
mentioning
confidence: 99%
“…However, Karabinus et al (1990) recorded a high incidence of chromatin instability and a low proportion of intact acrosomes in spermatozoa of young bulls. Furthermore, in a recent study on dairy sheep in our lab, Lymberopoulos et al (2010) observed that mature rams had signifi cantly lower values of sperm hyperactive motility and peroxidized sperm, greater percentages of sperm with intact plasma membrane, functional mitochondria and condensed chromatin, as well as greater lambing rate and ewe prolifi cacy. These results are in accordance with the results of our investigation, in which young boars demonstrated higher values of sperm morphological abnormalities, chromatin instability and sperm head length than mature boars after 24 h of semen storage.…”
Section: Discussionmentioning
confidence: 74%